The effectiveness of mental health education on improving adolescents’ knowledge of depression prevention - Ruswadi, Indra; Wennie, Jummai; Masliha, Masliha (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2025)
Background: Mental health problems, particularly depression, among adolescents in a community have become a growing public health concern globally. Early preventive efforts are essential to reduce the burden of depression. Educational interventions in the community are one of the recommended strategies.Objectives: This study aimed to determine the effectiveness of mental health education in increasing adolescents’ knowledge of depression prevention in a community. Methods: This study employed a pre-experimental one-group pretest-posttest design involving 60 adolescents selected through purposive sampling in a rural community setting. The data were collected using a validated knowledge questionnaire on depression prevention and analysed using paired-sample t-tests in SPSS version 28. Results: The findings revealed a significant increase in the mean knowledge score after the intervention (pretest mean = 11.82 ± 2.41; posttest mean = 16.45 ± 1.89; p < 0.001). These results indicate that the mental health education intervention effectively improves adolescents’ knowledge of depression prevention.Conclusion: Mental health education can be an effective strategy in improving adolescent knowledge of depression prevention in community settings. This finding supports the importance of community-based educational programs as part of sustainable mental health promotion aligned with the Sustainable Development Goals.